2023
DOI: 10.3389/fpsyg.2023.1124095
|View full text |Cite
|
Sign up to set email alerts
|

Impact of academic cheating and perceived online learning effectiveness on academic performance during the COVID-19 pandemic among Pakistani students

Abstract: ObjectiveThe study was conducted to examine academic cheating behaviors and perceived online effectiveness on academic performance during the period of COVID-19 among schools, colleges, and university students in Pakistan.MethodologyA cross-sectional research design was used in the current study. Convenience sampling was used to collect the data. The study included a total sample of N = 8,590 students, with males (n = 3,270, 38%) and females (n = 5,320, 61%) participating. The data was divided into three categ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…It led to high levels of academic dishonesty. Several finding supports this claim and found a significant increase in academic dishonesty during the Covid-19 pandemic timeframe (Comas-Forgas et al, 2021;Jenkins et al, 2023;Malik et al, 2023). One factor contributing to cheating, which is linked to decision-making, is that cheating takes place based on the presence of opportunities (Adzima, 2020).…”
Section: Introductionmentioning
confidence: 70%
See 1 more Smart Citation
“…It led to high levels of academic dishonesty. Several finding supports this claim and found a significant increase in academic dishonesty during the Covid-19 pandemic timeframe (Comas-Forgas et al, 2021;Jenkins et al, 2023;Malik et al, 2023). One factor contributing to cheating, which is linked to decision-making, is that cheating takes place based on the presence of opportunities (Adzima, 2020).…”
Section: Introductionmentioning
confidence: 70%
“…At the beginning of the pandemic, all learning processes had to be switched to online. Many researchers have investigated the effect of switching learning to online on academic dishonesty (e.g., Erguvan, 2021;Janke et al, 2021;Jose, 2022;Malik et al, 2023). Most studies found an increasing number of academic dishonesty when learning mode had to switch to online.…”
Section: Introductionmentioning
confidence: 99%
“…Studies suggest that ethical problems exist across many disciplines internationally [ 18 , 37 ]. For instance, using data collected from 224 undergraduate students in the United Arab Emirates, Khan and Balasubramanian [ 25 ] reveal that students admitted to cheating by using technology.…”
Section: Students’ Ethical Issuesmentioning
confidence: 99%
“…Many studies conducted in the field of education and psychology aim to compare unethical behaviors in e-learning settings and face-to-face settings (e.g., Refs. [ 37 , [44] , [45] , [46] ]). In a survey of 214 undergraduates at a large southeastern university, Jenkins et al [ 45 ] found that the COVID-19 pandemic increased students' first-time cheating and made students more creative in cheating with faculty who tried to combat dishonest behavior.…”
Section: Students’ Ethical Issuesmentioning
confidence: 99%
“…The sudden shift to online platforms has both advantages and disadvantages. Digital education makes materials more accessible, potentially reducing inequities and offers flexibility for students (Malik et al, 2023). Digital learning has enhanced technological skills for both students and teachers, making them more valuable in today's increasingly tech-driven work market (Kumar et al, 2022).…”
Section: Educational Policies and Investmentmentioning
confidence: 99%